Impact of Olive Oil Constituents on C-reactive Protein : In silico Evidence - Hidayat Ur, Rahman; Muhammad Hamdi, Mahmood; Najm Us, Sama; Muhammad, Afzal; Mohd Razip, Asaruddin; Mohammed Safwan, Ali Khan (Japan Oil Chemists’ Society, 2022)
Pain is a sensation a humans sense as a protective mechanism against physical injury. This sensation is closely related to inflammation. It ranges from mild to highly obnoxious. It is well-known that the levels of the inflammatory biomarker, C-reactive protein (CRP), increase manifold in acute inflammation and pain. Olive oil, known to have many phytochemicals, has been traditionally used to alleviate pain. Amongst major phenolic compounds in olive oil are oleuropein (OLE), hydroxytyrosol (HT), tyrosol, and oleocanthal. Whether the analgesic and anti-inflammatory properties in olive oil are due to any specific interections is not known. Therefore, this study aimed to elucidate the possible anti-inflammatory and anti-nociceptive properties in those major phenolic compounds by using molecular docking software MOE 2015, comparing the energy value and binding site of phenolic compounds to that of well-known synthetic non-steroidal anti-inflammatory drugs (NSAIDs) and phosphocholine. The docking experiment showed that all compounds could directly interact with CRP. Oleuropein had the most potent interaction with CRP (–7.7580), followed by indomethacin (–6.0775), oleocanthal (–5.5734), ibuprofen (–5.3857), phosphocholine (–4.3876), HT (–4.2782), and tyrosol (–4.2329). Interestingly, the present study found other phytochemicals in olive oil that can be exploited as potential, safe, and cost-effective lead compound(s) for analgesic and anti-inflammatory activity, as supported by its molecular docking data.